2016
DOI: 10.1016/j.jacc.2016.06.060
|View full text |Cite
|
Sign up to set email alerts
|

Hyperkalemia in Heart Failure

Abstract: Disorders of potassium homeostasis can potentiate the already elevated risk of arrhythmia in heart failure. Heart failure patients have a high prevalence of chronic kidney disease, which further heightens the risk of hyperkalemia, especially when renin-angiotensin-aldosterone system inhibitors are used. Acute treatment for hyperkalemia may not be tolerated in the long term. Recent data for patiromer and sodium zirconium cyclosilicate, used to treat and prevent high serum potassium levels on a more chronic basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 76 publications
0
55
0
11
Order By: Relevance
“…Emerging data with novel potassium binders reducing the risk of hyperkalemia may further facilitate such a study. 10 Spironolactone is a prodrug that is converted to active metabolite canrenone, which is responsible for its mineralocorticoid effects. 15 Considering the short duration of AHF hospitalizations in the United States averaging at 4–5 days, 16 using intravenous canrenoate with faster onset of action may be more beneficial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging data with novel potassium binders reducing the risk of hyperkalemia may further facilitate such a study. 10 Spironolactone is a prodrug that is converted to active metabolite canrenone, which is responsible for its mineralocorticoid effects. 15 Considering the short duration of AHF hospitalizations in the United States averaging at 4–5 days, 16 using intravenous canrenoate with faster onset of action may be more beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…8, 9 However, there have been concerns regarding hyperkalemia and renal failure with MRA use especially with high doses. 10 A single-center, single-blind, non-randomized, trial suggested benefit with high dose MRA therapy in AHF, including lower natriuretic peptide levels, less congestion, better renal function, and less need for intravenous diuretic. 11 Accordingly, we performed the Aldosterone Targeted NeuroHormonal CombinEd with Natriuresis TherApy in Heart Failure (ATHENA-HF) trial to test the hypothesis that high dose spironolactone use in patients with AHF will have a beneficial impact in patients with AHF.…”
mentioning
confidence: 99%
“…Guideline-directed medical therapy with RAASi has oft been implicated as a major factor in the development of hyperkalemia in patients with HF, CKD, and/or DM. The development of hyperkalemia in patients with cardiac or renal disease prescribed RAASi poses a therapeutic dilemma, as those patients who are at highest risk for hyperkalemia are the same who may derive the greatest cardiovascular benefit from these medications [18,19].…”
mentioning
confidence: 99%
“…A krónikus rekurráló hyperkalaemia veszélyét jelenleg a kacsdiuretikumok dózisának növelésével, a RAASi-k adagjának csökkentésével, vagy a kombinációban tör-ténő alkalmazásuk megszüntetésével, végső esetben elhagyásukkal, nagyfokú vesefunkció-romlás esetén, tartós hemodialízis alkalmazásával csökkenthetjük (26). Ezeknek az eljárásoknak az előnytelen és körül-ményes volta közismert.…”
Section: A Hyperkalaemia Tartós Kezelésének Jelenlegi Lehetőségeiunclassified
“…A RAASi-kezelés felfüggesztése, dózis csökken-tése nemkívánatos válasznak tekinthető a problémára. Mivel a nagy kontrollált tanulmányokban a magas hyperkalaemia rizikónak kitett betegek, az előrehaladott vesebetegségben szenvedők, valamint az idős betegek nincsenek reprezentálva, a szívelégtelenség gyógysze-res kezelésében jelenleg egy nagy betegcsoportot érin-tő kritikus evidenciahiánnyal állunk szemben (26). Az evidenciahiány által érintett betegek jelentős hányada válhatna kezelhetővé, ha a hyperkalaemia veszélyét tartósan, súlyos mellékhatások nélkül képesek lennénk csökkenteni.…”
Section: Evidenciák áLtal Válasz Nélkül Hagyott Kérdések -Perspektívákunclassified